The Causal Effect of Tracing by Peer Health Workers on Return to Clinic Among Patients Who Were Lost to Follow-up From Antiretroviral Therapy in Eastern Africa: A "Natural Experiment" Arising From Surveillance of Lost Patients. (17th March 2017) - Bershetyn, Anna; Odeny, Thomas A.; Lyamuya, Rita; Nakiwogga-Muwanga, Alice; Diero, Lameck; Bwana, Mwebesa; Braitstein, Paula; Somi, Geoffrey; Kambugu, Andrew; Bukusi, Elizabeth; Hartogensis, Wendy; Glidden, David V.; et al.
Summary: Successful contact with patients lost to follow-up from HIV care has a strong, short-term effect on return to care, but is of limited overall efficiency because many patients have died, are not found in person, or are in care elsewhere. Abstract: Background: The effect of tracing human immunodeficiency virus (HIV)–infected patients who are lost to follow-up (LTFU) on reengagement has not been rigorously assessed. We carried out an ex post analysis of a surveillance study in which LTFU patients were randomly selected for tracing to identify the effect of tracing on reengagement. Methods: We evaluated HIV-infected adults on antiretroviral therapy who were LTFU (>90 days late for last visit) at 14 clinics in Uganda, Kenya, and Tanzania. A random sample of LTFU patients was selected for tracing by peer health workers. We assessed the effect of selection for tracing using Kaplan-Meier estimates of reengagement among all patients as well as the subset of LTFU patients who were alive, contacted in person by the tracer, and out of care. Results: Of 5781 eligible patients, 991 (17%) were randomly selected for tracing. One year after selection for tracing, 13.3% (95% confidence interval [CI], 11.1%–15.3%) of those selected for tracing returned compared with 10.0% (95% CI, 9.1%–10.8%) of those not randomly selected, an adjusted risk difference of 3.0% (95% CI, .7%–5.3%). Among patients found to be alive, personally contacted, and out of care, tracing increased the absolute probability of return at 1 year by 22% (95% CI, 7.1%–36.2%). The effect of tracing on rate of return to clinic decayed with a half-life of 7.0 days after tracing (95% CI, 2.6 %–12.9%). Conclusions: Tracing interventions increase reengagement, but developing methods for targeting LTFU patients most likely to benefit can make this practice more efficient.